Parallel computational fluid dynamics : new frontiers and multi-disciplinary applications : proceedings of the Parallel CFD 2002 Conference, Kansai Science City, Japan (May 20-22, 2002) /: new frontiers and multi-disciplinary applications : proceedings of the Parallel CFD 2002 Conference, Kansai Science City, Japan (May 20-22, 2002). (2003) - Unknown
No abstract available